2023
DOI: 10.2967/jnumed.122.265355
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of134Ce/134La as a PET Imaging Theranostic Pair for225Ac α-Radiotherapeutics

Kondapa Naidu Bobba,
Anil P. Bidkar,
Niranjan Meher
et al.

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Unchelated [ 134 Ce]CeCl 3 and [ 225 Ac]AcCl 3 are mostly similar in their biodistribution in mice, with the major difference being the higher spleen uptake found for 134 Ce. Once incorporated in a radiotracer, the radiometals make for a good pharmacokinetic match, as indicated in this study and recent literature [5, 6, 8, 10].…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Unchelated [ 134 Ce]CeCl 3 and [ 225 Ac]AcCl 3 are mostly similar in their biodistribution in mice, with the major difference being the higher spleen uptake found for 134 Ce. Once incorporated in a radiotracer, the radiometals make for a good pharmacokinetic match, as indicated in this study and recent literature [5, 6, 8, 10].…”
Section: Discussionmentioning
confidence: 58%
“…This PET in vivo generator is currently undergoing preclinical investigation in cancer research as a diagnostic match for actinium-225 ( 225 Ac, t ½ =9.9 d) [5][6][7][8]. Over the last decade, 225 Ac has been developed into potent drug constructs targeting various forms of mostly highly aggressive and even treatmentresistant cancers.…”
Section: Introductionmentioning
confidence: 99%
“…To prepare for the TRTs, Nb HER2 (WT) and Nb HER2 (FSY) were conjugated with Macropa-PEG 4 -TFP ester (Figure A). Macropa was chosen as the chelator, as recent data have shown that it chelates 225 Ac efficiently. , Mass spectrometric analysis of the conjugated samples confirmed that both Nb HER2 (WT) and Nb HER2 (FSY) were successfully conjugated with Macropa-PEG 4 , showing two peaks of approximately equal intensity corresponding to the unlabeled and singly labeled nanobody, respectively (Figure B). To ensure that the conjugation of Macropa-PEG 4 did not affect the nanobody’s covalent cross-linking ability, we incubated Macropa-PEG 4 -Nb HER2 (WT) or Macropa-PEG 4 -Nb HER2 (FSY) with and without the HER2 ECD at 37 °C for up to 2 h and analyzed the samples via Western blot (Figure C).…”
Section: Resultsmentioning
confidence: 85%
“…Macropa-PEG 8 -TFP ester was synthesized by reacting the intermediate 1 in the presence of DIPEA in DMF followed by prep HPLC purification in 34% yield (Reaction scheme S1 and Figure S1 -S3). Macropa NCS was synthesized according to the reported literature 32 , and Macropa-PEG 4 -TFP was synthesized as per our prior publication 33 . With these derivatives in hand, the bifunctional chelators were conjugated to lysine residues on the antibody YS5 (Figure 1 A, B) 24 .…”
Section: Resultsmentioning
confidence: 99%
“…This isotope undergoes decay to 134 La (t 1/2 = 6.45 min) via electron capture. Subsequently, it further decays to stable 134 Ba through positron emission (63% β + ; endpoint energy, 2.69 MeV) 33 . This strategy has particular promise for the development of theranostics, owing to the chemical similarity between Ce 3+ and Ac 3+ , as well as the high fraction of positrons emitted by the daughter isotope 134 La 34 .…”
Section: Introductionmentioning
confidence: 99%